2001
DOI: 10.1103/physrevstab.4.044201
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal holes in debunched particle beams in storage rings, perpetuated by space-charge forces

Abstract: Stationary, self-consistent, and localized longitudinal density perturbations on an unbunched chargedparticle beam, which are solutions of the nonlinearized Vlasov-Poisson equation, have recently received some attention. In particular, we address the case that space charge is the dominant longitudinal impedance and the storage ring operates below transition energy so that the negative mass instability is not an explanation for persistent beam structure. Under the customary assumption of a bell-shaped steadysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Interestingly, the Vlasov equation (4.1) resulting from the hodograph transformation of the Benney equation is exactly the same as the equation that regulates coasting proton beams in particle accelerators (see for example [32] where a bunching term is also included). Now, this is a very remarkable fact: the integrability of the Vlasov-Benney equation implies soliton solutions, indications for which seem to have been found experimentally at CERN [21], BNL [2], LANL [9] and FermiLab [27]. (In the last case solitons are shown to appear even when a bunching force is present.)…”
Section: Applications Of the Kmlp Bracket And Quadratic Terms 41 Thementioning
confidence: 99%
“…Interestingly, the Vlasov equation (4.1) resulting from the hodograph transformation of the Benney equation is exactly the same as the equation that regulates coasting proton beams in particle accelerators (see for example [32] where a bunching term is also included). Now, this is a very remarkable fact: the integrability of the Vlasov-Benney equation implies soliton solutions, indications for which seem to have been found experimentally at CERN [21], BNL [2], LANL [9] and FermiLab [27]. (In the last case solitons are shown to appear even when a bunching force is present.)…”
Section: Applications Of the Kmlp Bracket And Quadratic Terms 41 Thementioning
confidence: 99%
“…Similar wave propagation was viewed on a coasting beam at the CERN Proton Synchrotron Booster by Koscielniak. 25 Simulations by Friedman 26 for Integrated Research Experiments and fusion drivers also exhibited similar waves launched from modulations in beam velocity.…”
Section: Experimental Results Of Longitudinal Beam Focusingmentioning
confidence: 69%
“…Recently, Koscielniak et al [10] reported formation of holes in the longitudinal density profile which has been predicted by computer simulations and observed at the CERN PS Booster and at Fermilab. Although it is not straightforward to compare our results with the findings of Koscielniak et al, it is worth noting that regardless of the case (longitudinal or transverse phase space) the nonlinear interaction between density waves in space-chargedominated beams as a rule leads to the formation of holes in the density profile.…”
Section: The Nonlinear Schrödinger Equation For a Single Modementioning
confidence: 99%
“…As a result, we obtain the new Hamiltonian 10) where the self-field potential U(x; θ) (φ = √ βU ) satisfies the equation…”
Section: Derivation Of the Hydrodynamic Modelmentioning
confidence: 99%
See 1 more Smart Citation